FTO First Intron rs1558902 Variant and Platelets Count in White Middle-aged Women: Prague Pre- and Post-Menopausal Females (3PMFs) Study. (February 2013) - Hubacek, Jaroslav A.; Dlouha, Dana; Lanska, Vera; Stavek, Petr; Pagacova, Libuse; Kralova-Lesna, Ivana; Pitha, Jan
The polymorphisms within the FTO gene play an important role in the genetic determination of body weight and body mass index and have been associated with cardiovascular disease, but the causal mechanism is still a matter of debate. The possible effect on the platelet count as a marker of hemocoagulation status as a possible cardiovascular risk factor was suggested in Japanese population. We have analyzed both rs1558902 FTO polymorphism (T > A) and platelet counts in the Prague Pre and Post Menopausal Females (3PMFs) study, including those of 669 women (mean age, 55.7 ± 2.7 years). The frequencies of the FTO genotypes were similar to other populations (TT, 30.4%; TA, 48.1%; and AA, 21.5%). We have not detected a significant association between the FTO rs1558902 variant and platelet counts in white women (TT, 242 ± 55 × 10 9 ; TA, 246 ± 67 × 10 9 ; and AA, 247 ± 55 × 10 9 ; F[2.642] = 0.30, P = 0.75). At least in white persons, platelet count seems not to be a link between the FTO variation and risk of cardiovascular disease.